2000
DOI: 10.1053/joca.1999.0264
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled, cross-over study of ginger extracts and Ibuprofen in osteoarthritis

Abstract: In the present study a statistically significant effect of ginger extract could only be demonstrated by explorative statistical methods in the first period of treatment before cross-over, while a significant difference was not observed in the study as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
190
0
10

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(203 citation statements)
references
References 8 publications
3
190
0
10
Order By: Relevance
“…Furthermore, impaired hepatic function may also have affected cholesterol metabolism leading to hypercholesterolemia and hypertriglyceridemia. While the observed improvement in the lipid/cholesterol homeostasis in the garlic supplemented diet fed group might be due to the hypocholesterolemic and hypolipidemic properties of garlic [31][32][33] . In addition, improvement in the liver function on the other hand could have contributed to this observed lipid homeostasis.…”
Section: Groups Treatments Triglyceridementioning
confidence: 99%
“…Furthermore, impaired hepatic function may also have affected cholesterol metabolism leading to hypercholesterolemia and hypertriglyceridemia. While the observed improvement in the lipid/cholesterol homeostasis in the garlic supplemented diet fed group might be due to the hypocholesterolemic and hypolipidemic properties of garlic [31][32][33] . In addition, improvement in the liver function on the other hand could have contributed to this observed lipid homeostasis.…”
Section: Groups Treatments Triglyceridementioning
confidence: 99%
“…In conventional Western medicine, ginger preparations are administered clinically to treat emesis, nausea, and migraine headache (2,3). Based on the widespread therapeutic use of ginger in Asia for the treatment of inflammatory diseases, several studies have been dedicated to the elucidation of potential anti-inflammatory mechanisms (4)(5)(6)(7). At relatively high mM concentrations, ginger constituents such as gingerols, shogaols, and diarylheptanoids have been reported to weakly inhibit components of proinflammatory signal transduction pathways in vitro, such as NF-kB, protein kinase C, and MAPKs (8,9).…”
mentioning
confidence: 99%
“…The efficacy of willow bark extract was confirmed by a statistically significant difference of 14% in the WOMAC pain dimension between the treatment and placebo groups [116]. Ginger extracts were associated with a reduction of pain on a VAS and the Lequesne Index in a randomized placebo-controlled clinical trial [115,119]. In evaluating the effectiveness of TCM in respiratory diseases [120], Xue et al used a combination of symptoms scores diaries, the Rhinoconjunctvitis and Rhinitis Quality of Life Questionnaire (RQLQ), patient's global evaluations of improvement and physician's objective evaluation in a multi-center randomized double-blind, placebo-controlled clinical trials on allergic rhinitis.…”
Section: Applications Of Hrqol Measures In Tcm Treatments Of Other Comentioning
confidence: 88%
“…The Seattle Angina Questionnaire (SAQ) [113] was used in coronary artery bypass grafting patients and found that combining TCM with conventional Western care can significantly improve the domains of angina stability, angina frequency, treatment satisfaction and disease perception measured by the SAQ when compared with conventional Western care [114]. In evaluating the effectiveness of TCM treatment on patients with osteoarthritis, the SF-36 Health Survey, SF-12 Health Survey, Visual Analog Scale (VAS), Western Ontario and McMaster University osteoarthritis index (WOMAC), Lequesne Index and Global Satisfaction Scale have all been used [115][116][117]. The effectiveness of Complementary and Alternative Medicine (CAM) clinic in relieving pain of OA patients by the combination usage of herbs, chiropractice and acupuncture was detected by the SF-12v2 Health Survey [117].…”
Section: Applications Of Hrqol Measures In Tcm Treatments Of Other Comentioning
confidence: 99%